If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1x = 5x + -41 Reorder the terms: 1 + -1x = -41 + 5x Solving 1 + -1x = -41 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + -1x + -5x = -41 + 5x + -5x Combine like terms: -1x + -5x = -6x 1 + -6x = -41 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -6x = -41 + 0 1 + -6x = -41 Add '-1' to each side of the equation. 1 + -1 + -6x = -41 + -1 Combine like terms: 1 + -1 = 0 0 + -6x = -41 + -1 -6x = -41 + -1 Combine like terms: -41 + -1 = -42 -6x = -42 Divide each side by '-6'. x = 7 Simplifying x = 7
| 7x+1=x+13 | | 2w^2-6w=0 | | 4x^2-25x+18=-6x+6 | | 9x-10=-x-18 | | 7(x+2)-4=8-x-14 | | (x-1)(3x+2)=0 | | x^2+x-13=-7x-4 | | 3y+7.569=24.069 | | x^2+2x+2=5 | | 3[-4(2x+4)+2(5x-3)]= | | 4x^2+8x+7=0 | | 5(y+3)=-10 | | x+10=-38-3x | | -3+6=-15 | | x^2+17x+17=0 | | 2[-4(4x+5)+5(4x-4)]= | | x^2+17x+17= | | (1-v)(4v-3)=0 | | 3y-12=5y | | 4x^2+23x+28=0 | | (x+4)(x-5)=-16 | | 6x^2-43x-40=0 | | w(11w+3)=8 | | 3x-8x=-25 | | X^2+a-72=0 | | r=m+mvk | | 3t^2-18t+8=0 | | L=2P+2W | | 5x+6=66-7x | | 4y-7=33 | | (2-w)(5w+4)=0 | | 0.4x^2+4x+8.4=0 |